Effect Of Inspection Errors And Preventive Maintenance On A Two-Stage Production Inventory System - Darwish, M. (2020)
The effect of imperfect production processes on lot-sizing decisions has received a lot of attention in the literature. These efforts have mostly been confined to single-stage production systems. The issue of imperfect production processes has not been adequately addressed in the context of multistage production/inventory systems. In this paper, we propose a production inventory model that takes into account the effect of imperfect production processes, preventive maintenance and inspection errors. Numerical examples are presented for illustrative purposes.